Growth of an anaerobic sulfate‐reducing bacterium sustained by oxygen respiratory energy conservation after O2‐driven experimental evolution. (3rd December 2018) - Schoeffler, Marine; Gaudin, Anne‐Laure; Ramel, Fanny; Valette, Odile; Denis, Yann; Hania, Wagdi Ben; Hirschler‐Réa, Agnès; Dolla, Alain
Summary: Desulfovibrio species are representatives of microorganisms at the boundary between anaerobic and aerobic lifestyles, since they contain the enzymatic systems required for both sulfate and oxygen reduction. However, the latter has been shown to be solely a protective mechanism. By implementing the oxygen‐driven experimental evolution of Desulfovibrio vulgaris Hildenborough, we have obtained strains that have evolved to grow with energy derived from oxidative phosphorylation linked to oxygen reduction. We show that a few mutations are sufficient for the emergence of this phenotype and reveal two routes of evolution primarily involving either inactivation or overexpression of the gene encoding heterodisulfide reductase. We propose that the oxygen respiration for energy conservation that sustains the growth of the O2 ‐evolved strains is associated with a rearrangement of metabolite fluxes, especially NAD + /NADH, leading to an optimized O2 reduction. These evolved strains are the first sulfate‐reducing bacteria that exhibit a demonstrated oxygen respiratory process that enables growth.